Preference of the Waterlily Aphid, Rhopalosiphum nymphaeae (Hemiptera: Aphididae) on Four Hostplants - Ilmam Zul Fahmi; Nugroho Susetya Putra; Siwi Indarti; Satoru Sato (Jurnal Perlindungan Tanaman Indonesia, 2021)
Waterlily aphid Rhopalosiphum nymphaeae is one of the aphids that have many hosts, including Azolla filiculoides, Limnobium laevigatum, Monochoria vaginalis and Spirodela polyrhiza. The aim of this study was to study the effect of host shift and confirm the results  of previous studies on the effect of nitrogen and carbon factors among A. filiculoides, L. laevigatum, M. vaginalis and S. polyrhiza on the level of aphid preference and number of offspring. Analysis of the nitrogen and carbon content of plants was also carried out to confirm the preference and number of offspring produced by aphids. The study began with maintaining aphids on the four tested hosts, up to the 4th generation. Twenty five individuals were randomly selected from each host, then released on the inner wall of the plastic container (14 x 7.5 x 15 cm3) which was filled with four hosts arranged side by side. Observations were made every 24 hours up to 97 hours starting from the first hour after treatment. Observations after 97 hours showed that waterlily aphids imago preferred L. laevigatum the most (49.28%), then on M. vaginalis (20.43%), S. polyrhiza (16.33%), and A. filiculoides (1.75%). Meanwhile, the number of offspring produced by each group of aphids that selected on four hosts were: 46.65 individuals on L. laevigatum, 37.8 individuals on M. vaginalis, 19 individuals on S. polyrhiza, and 0.6 individuals on A. filiculoides. The analysis showed that the highest nitrogen content was found in M. vaginalis (4.16%), followed by S. polyrhiza (3.71%), L. laevigatum (2.33%), and A. filiculoides (2.08%).